Comparison of Force Decay of Two Different Types of Elastomeric Chains with the Use of Different Types of Mouth Washes – An In vitro Study - Rahul Pawar; Tanmoy Majumder; Shalini Singh; Dip G. Choudhury; Md Kamal Hassan; Swati Mrinal (Journal of Pharmacy and Bioallied Sciences)
Background: Elastomeric chains are commonly used in orthodontic treatments to apply continuous force for tooth movement. However, the exposure of these chains to different mouthwashes can impact their force retention and effectiveness. Understanding the effect of various mouthwash solutions on elastomeric chains is crucial to optimize orthodontic treatment outcomes and maintain the desired level of force over time. This study investigates the impact of different mouthwash solutions on the force decay of both prestretched and unstretched elastomeric chains, providing insights into the best practices for mouthwash use during orthodontic care. Material and Methods: A study was conducted using 1000 specimens of “five-unit clear short-linked elastomeric chains.” These specimens were divided into two main groups of elastomeric chains: prestretched and unstretched. Each main group was further subdivided into five subgroups: one control (artificial saliva) and four test subgroups exposed to different mouthwashes. Statistical analysis was conducted with a significance level set at P < 0.05 to determine the effect of each mouthwash on the force retention of the elastomeric chains. Results: The initial force levels of elastomeric chains before and after immersion in various solutions over different time intervals showed statistically significant differences. These differences were observed in both prestretched and unstretched elastomeric chain groups as well as between the prestretched and unstretched conditions. The results indicate that different mouthwash solutions have varying impacts on force decay, with some solutions leading to more pronounced degradation than others. Conclusion: Common mouthwashes degrade the force of both prestretched and unstretched elastomeric chains. To minimize this effect during orthodontic treatment, it is recommended to use Himalaya HiOra, probiotic, and Clohex® mouthwashes, followed by fluoride mouthwash. These alternatives may help preserve the force retention of elastomeric chains and improve treatment efficacy.